2016
DOI: 10.1128/mbio.01753-16
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Quenching of Nitrobacter winogradskyi Suggests that Quorum Sensing Regulates Fluxes of Nitrogen Oxide(s) during Nitrification

Abstract: Quorum sensing (QS) is a widespread process in bacteria used to coordinate gene expression with cell density, diffusion dynamics, and spatial distribution through the production of diffusible chemical signals. To date, most studies on QS have focused on model bacteria that are amenable to genetic manipulation and capable of high growth rates, but many environmentally important bacteria have been overlooked. For example, representatives of proteobacteria that participate in nitrification, the aerobic oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 56 publications
3
29
0
Order By: Relevance
“…Toyofuku et al (26) reported that P. aeruginosa quorum-sensing regulators LasR and RhlR could inhibit denitrification. Similarly, Nitrobacter winogradskyi significantly increased the expression of nirK and nirK cluster genes (genes involved in denitrification) after quorum quenching (27). In our study, the addition of NaNO 3 or NaNO 2 changed the rate of denitrification (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Toyofuku et al (26) reported that P. aeruginosa quorum-sensing regulators LasR and RhlR could inhibit denitrification. Similarly, Nitrobacter winogradskyi significantly increased the expression of nirK and nirK cluster genes (genes involved in denitrification) after quorum quenching (27). In our study, the addition of NaNO 3 or NaNO 2 changed the rate of denitrification (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Our current model does not consider acyl-homoserine lactone quorum sensing (QS) regulation of NO production proposed in recent work by Mellbye et al due to insufficient data on the kinetic effects of QS regulation (16). The genome-scale model also does not consider the minute N 2 O production observed by N. winogradskyi , since its genome does not contain any known NOR-encoding gene.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular NH 2 OH concentration was measured by chemical assay as previously described (58, 59). NO and NO 2 (NO x ) concentrations in the headspace were measured using a portable NO 2 analyzer/NO x converter (LMA-3D and LNC-3D; Unisearch Associates Ltd., Concord, Ontario, Canada), and N 2 O concentration was measured by gas chromatography as previously described (16, 21). …”
Section: Methodsmentioning
confidence: 99%
“…Using a novel quorum quenching coupled with mRNA sequencing approach, Mellbye et al . () revealed that QS signalling influences production and consumption of NO, NO 2 and N 2 O in a model nitrite oxidizer, Nitrobacter winogradskyi . QS mediated expression of genes can also regulate inter/intra kingdom signalling in microbiome.…”
Section: The Potential Of Emerging Microbiome‐based Technologies For mentioning
confidence: 99%
“…However, this approach may have indirect effects on other Ncycling processes, as these microbes have strong and constant associations and closely interact with each other to produce N 2 O (Butterbach-Bahl et al, 2013). Using a novel quorum quenching coupled with mRNA sequencing approach, Mellbye et al (2016) revealed that QS signalling influences production and consumption of NO, NO 2 and N 2 O in a model nitrite oxidizer, Nitrobacter winogradskyi. QS mediated expression of genes can also regulate inter/intra kingdom signalling in microbiome.…”
Section: Mozzola 2002mentioning
confidence: 99%